Citizen participation and climate change: social perceptions about climate change - a case study in the Central Region of Portugal - Alves, Fátima (2022)
Research on social perceptions and effective participation about Climate Change (CC) appears to be a critical component of the socio-political contexts in which CC mitigation and adaptation plans and the necessary political and behavioral change for the ecological transition are developed. This study sought to develop itself as a strategy to involve populations in the elaboration of Climate Change Local Adaptation Plans, through a questionnaire survey applied online.